In silico assessment of flavonoids from Matricaria chamomilla for anti-psoriatic potential via molecular docking and ADME/T profiling - V. V. Rajesham; Pentu, Narendra; Kumar, Pasupuleti Kishore; T. Rama Rao; Morsu, Ashok (Creative Pharma Assent, 2025)
Background: Computational tools are advancing in the drug discovery process to assess the safety profiles of new compounds with reduced investment. Herbal remedies exhibit a diverse range of active compounds that can alleviate various disease conditions with fewer side effects. Method: This study investigates the molecular docking of phytochemicals from Matricaria Chamomilla against inflammation-induced skin disorders, such as psoriasis. Using AutoDock Vina and MGL Tools, key compounds were evaluated for binding affinity with target proteins. ADMET analysis, as assessed by pkCSM and SWISSADME, to predict the Lipinski’s Rule of Five. Redocking was implemented to confirm the binding affinity of the docked position. Results: This molecular docking of phenolic compounds and flavonoids, including quercetin, apigenin, rutin, luteolin, and various glycosylated derivatives—from Matricaria Chamomilla against cellular proteins implicated in psoriasis (PDE-4, p38MAPK, IL-23, BTK, JAK-3, TNF-α, IL-17A, and IL-6). Using Autodock Vina and MGL Tools, rutin and quercetin demonstrated favourable binding affinities. At the same time, luteolin-7-glycoside exhibited the highest docking scores (e.g., -10.8 kcal/mol for PDE-4, -9.7 kcal/mol for JAK-3, and -9.1 kcal/mol for TNF-α) compared to the standard. Results highlight the potential of chamomile phytochemicals as safe, orally effective agents for managing inflammatory skin conditions. Redocking confirms the RMSD values are within the limits of < 2 A0. Conclusion: The data suggest that chamomile flavonoids could be safe and beneficial for treating inflammatory diseases and psoriasis. Although enzymatic and cell-based assays, along with further preclinical evaluations, are essential for advancing research in disease modification, formulation strategies play a role in improving drug characteristics